Licensing Procedures for Palm Oil Mills in North Sumatra: Integration of Investment Law and Regional Ecological Impacts - Udin Silalahi; Joy Zaman Felix Saragih; Frederick Xaverius Tjipto; Dilla Elfira Damanik; Nadya E. Hutagaol (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
North Sumatra plays a vital role in Indonesia’s palm oil industry thanks to the region’s extensive plantation areas and high level of processing. The development of Palm Oil Processing Plants (PPKS) is governed not only by plantation regulations but also by Law No. 25 of 2007 on Investment, which adopts principles of sustainability and environmental responsibility. This research aims to examine and evaluate the level of integration between policies that promote investment facilitation and the obligation to control environmental impacts in the POM licensing process at the regional level. This research uses a normative juridical method with a qualitative descriptive approach, focusing on the examination of applicable licensing regulations and their implementation in the region. Based on the results of the analysis, it is known that the application of the risk-based licensing system has had a positive impact in improving investment process efficiency. However, this improvement has not been fully accompanied by the effectiveness of environmental supervision. This condition is reflected in the persistence of environmental problems, such as the decline in river water quality and increasing greenhouse gas emissions in several locations. These findings indicate that strengthening post-licensing supervision is a very crucial matter to undertake. In addition, closer integration between investment policy and environmental protection instruments is also needed in order to create a balance between economic growth and environmental sustainability. Thus, the development of the palm oil industry is expected to proceed in a sustainable and responsible manner.